Impact of Violent Victimization on Physical and Mental Health Among Women in the United States, 1994-1996 - Kaukinen, Catherine E. ([Verlag nicht ermittelbar], 2007)
The major goals of the project were to use survey data about victimization experiences among American women to examine: (a) the consequences of victimization for women's physical and mental health, (b) how the impact of victimization on women's health sequelae is conditioned by the victim's invoking of family and community support, and (c) how among victims of intimate partner violence, such factors as the relationship between the victim and offender, the offender's characteristics, and police involvement condition the impact of victimization on the victim's subsequent physical and mental health. This data collection consists of the SPSS syntax used to recode existing variables and create new variables from the study, VIOLENCE AND THREATS OF VIOLENCE AGAINST WOMEN AND MEN IN THE UNITED STATES, 1994-1996 (ICPSR 2566). The study, also known as the National Violence against Women Survey (NVAWS), surveyed 8,000 women 18 years of age or older residing in households throughout the United States in 1995 and 1996. The data for the NVAWS were gathered via a national, random-digit dialing sample of telephone households in the United States, stratified by United States Census region. The NVAWS respondents were asked about their lifetime experiences with four different kinds of violent victimization: sexual abuse, physical abuse, stalking, and intimidation. Using the data from the NVAWS, the researchers in this study performed three separate analyses. The study included outcome variables, focal variables, moderator variables, and control variables.